0.8x-0.4(60+x)=0.067(60)

Simple and best practice solution for 0.8x-0.4(60+x)=0.067(60) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.8x-0.4(60+x)=0.067(60) equation:


Simplifying
0.8x + -0.4(60 + x) = 0.067(60)
0.8x + (60 * -0.4 + x * -0.4) = 0.067(60)
0.8x + (-24 + -0.4x) = 0.067(60)

Reorder the terms:
-24 + 0.8x + -0.4x = 0.067(60)

Combine like terms: 0.8x + -0.4x = 0.4x
-24 + 0.4x = 0.067(60)

Multiply 0.067 * 60
-24 + 0.4x = 4.02

Solving
-24 + 0.4x = 4.02

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '24' to each side of the equation.
-24 + 24 + 0.4x = 4.02 + 24

Combine like terms: -24 + 24 = 0
0 + 0.4x = 4.02 + 24
0.4x = 4.02 + 24

Combine like terms: 4.02 + 24 = 28.02
0.4x = 28.02

Divide each side by '0.4'.
x = 70.05

Simplifying
x = 70.05

See similar equations:

| 0.18y+0.03(y+6000)=810 | | (2x+2)=-4 | | 16x^7-x^3-65= | | 3/4÷2= | | 6(2/3-3) | | 14x-2(2x-4)=9x+9 | | 4x^4+12x^7=0 | | X+100=-235 | | 8.3x+5=9.7x-1 | | 121x^2-324= | | -9/-3*2/-5*8 | | x+x-28=152 | | -5/6t=15 | | y=2x^2+12x-39 | | 9a^3-5a^3= | | (x^4-25)(x^2-1)=0 | | 0.05*(x^90)=5 | | 12x+3=18x-3 | | 27w/-12w | | 4(m+4)+8(-12m+11)=m-8+8m+11 | | 8(w-84)=88 | | 81=-9(j+87) | | 5(p-65)=85 | | -7(t-9)+2t=-8+t | | 27-m=8 | | 2x/4-1/4=x/3-7/3 | | 4a-11=9+3a | | 5(-6+1)-4n=-5+2n | | 24=-3(t+-24) | | 2(n-52)-22=2 | | 2(t-64)=56 | | 67-z=40 |

Equations solver categories